Terapi Kognitif Perilaku untuk Mengurangi Masalah Perilaku pada Anak Conduct Disorder - Dinda Septiani; Eka Ervika (JIP (Jurnal Intervensi Psikologi), 2011)
This research goals is to know whether problem solving skill training (PSST) can be effective to decrease conduct problem to a child with conduct disorder. Problem solving skill training is a form of cognitive behavior therapy (CBT), which PSST is a cognitive therapy that will be combined with behavior therapy token economy. Data collected method is interview, observation and CBCL. Data analysis method is qualitative analyzing. Result indicates that subject's conduct disorder behavior is decreased. Subject seldom fight or hit and used weapon that can cause physical harm to others. He seldom lying, never stealing and his compliance is increased too. This condition shows problem solving skill training can be used as therapy to decrease conduct problem to children with conduct disorder.Key Words: Conduct Disorder, Cognitive Behavior Therapy, Problem Solving Skill Training.